Real-Time Optimization of RISC-V Processors Based on Branch Prediction and Division Data Dependency - Zhiwei Jin; Hesong Di; Tingpeng Hu; Peng Wang (Applied Sciences)
Whether a processor can meet the real-time requirements of a system is a crucial factor affecting the security of real-time systems. Currently, the methods for evaluating hardware real-time performance and the quality of real-time performance are not comprehensive. To address these issues, a “Hardware Real-Time Parameter (Hrtp)” is proposed, which integrates the concepts of “whether it meets real-time system requirements”, “execution speed”, and “operational stability”. This parameter is used to evaluate the real-time performance of RISC-V processors before and after optimization. The processor is optimized for real-time performance using a “simplified local history branch predictor” and a “division data dependency module”. Experimental results show that the processor’s branch prediction accuracy and division calculation speed have both improved. When running the CoreMark benchmark program and the division test program, the test results improved, indicating an enhanced “real-time” performance of the hardware. The changes in the “Standalone Hardware Real-Time Performance Parameter (Hrtp)” data are consistent with theoretical analysis, and it can meet the evaluation needs for “hardware real-time performance”.